Bioautographic Analysis And Antibacterial Activity Test Of Mengkudu Leaf (Morinda Citrifolia L.) Ethanol Extract On The Bacteria Propionibacterium Acnes - Rati Satri Situmorang; Haris Munandar Nasution; Minda Sari Lubis; Yayuk Putri Rahayu (CV. Inara, 2022)
Noni contains alkaloids, flavonoids, tripertinoid, protein, lime, iron, carotene, glycosides antarkiron. The content of anthraquinin, scaloptin, flavonoid and adaptogen compounds are active compounds that have antifungal and antimicrobial effects. The antibiotics commonly used are antibiotics such as tetracycline, clindamycin and others. These chemical-based antibacterials have many negative side effects, therefore other alternatives are needed as antibacterials, one of which is by using noni. This study aims to analyze bioautography and determine the antibacterial activity of noni leaf ethanol extract against Propionibacterium acnes bacteria.This research was conducted experimentally using noni leaf ethanol extract with concentrations of 30%, 40%, 50% as independent variables and bioautographic analysis and antibacterial activity as dependent variables. The bioautography analysis was performed using TLC and the antibacterial activity test was performed using paper discs.The results of antibacterial testing of noni leaf ethanol extract with a concentration of 30% had an inhibition zone of 8.36 mm with a medium category, a concentration of 40% had an inhibition zone of 10.3 mm with a strong category and a concentration of 50% had an inhibition zone of 11.1 mm in a strong category. positive control tetracycline 30µg had an inhibition zone of 20.8 mm which was categorized as very strong. The results of the bioautography test using contact bioautography using the mobile phase of chloroform: n-hexane (7:3). The inhibition zone was obtained at an Rf value of 0.17, and the characteristics of the chromatogram spots were carried out by spraying 10% FeCl3 suspected that the spots were flavonoid compounds.